A contribution to the systematics of Salea anamallayana (Beddome, 1878) and S. horsfieldii Gray, 1845 (Squamata: Agamidae: Draconinae) - Das, Sunandan; Campbell, Patrick D.; Deuti, Kaushik; Bag, Probhat; Raha, Sujoy (Zootaxa, 2019)
Salea anamallayana (Beddome, 1878) and S. horsfieldii Gray, 1845 are two endemic montane forest dwelling draconine agamid lizards from the Western Ghats (India). The original descriptions of these two species were brief and apart from their inclusion in general faunal works, they have never been the focus of a rigorous taxonomic study. In this paper we provide a detailed redescription of the types of those two species. We also reconfirm the status of the subjective synonyms of those two species. We conducted a test of niche conservatism and on the basis of the results of this analysis, we demonstrate that in spite of occurring in apparently analogous habitats, the niche of the two species have diverged significantly. We also provide notes on the distribution and natural history of S. anamallayana and S. horsfieldii.